Ethical dilemmas of contemporary business - Stanisław Ciupka (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2023)
The article argues that the goal of business is to increase profit, but it also recognizes that proper relationships must exist between the entrepreneur and employees, customers, the state, and society at large. These relationships are deemed necessary for business to occur, and additional relationships, such as those with contractors, the media, and the natural environment, may also be relevant. The ethical aspects of business are inseparable from the ethical problems present in society. Undesirable behaviors within business activities are discussed as morally reprehensible, affecting both business conduct and generating moral dilemmas within society. Economic issues are noted as playing a significant role in contemporary society, often becoming modern idols. Consequently, there is a growing call for proper ethical conduct in the business world to address these concerns and ensure the common good. The article highlights that answers within the realm of business ethics are influenced by researchers' ethical and economic perspectives. The distinction between entrepreneurs and managers is emphasized, with the latter often assuming entrepreneurial roles. This separation raises concerns regarding the alignment of owners' moral obligations with the goals and commitments of managerial staff. Shareholder interests, primarily focused on profit maximization, sometimes